1972
DOI: 10.1083/jcb.54.2.232
|View full text |Cite
|
Sign up to set email alerts
|

The Polarity of the Proximal Tubule Cell in Rat Kidney

Abstract: Two different membrane fractions were obtained from a brush-border fraction of rat kidney cortex by using their different electrical surface charges in preparative free-flow electrophoresis. One membrane fraction contained only morphologically intact microvilli and was characterized by a high specific activity of alkaline phosphatase. The other fraction morphologically resembled classical plasma membranes by possessing junctional complexes and a high Na-K-ATPase activity The contamination of the isolated membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(46 citation statements)
references
References 13 publications
1
45
0
Order By: Relevance
“…In fact, the inhibition of the transport enzyme Na-K-ATPase (30) suggests the occurrence of a defective ATP synthesis. In our study, major membranous changes were seen at the base of the cell where the Na-K-ATPase involved in active transport is localized (31)(32)(33)(34). While the brush border structure of the proximal nephron appeared to be well preserved (28,29) (35), who showed that maleic anhydride reacts rapidly and specifically with amino groups associated with the protein fraction of the red cell membrane.…”
Section: Introductionmentioning
confidence: 80%
“…In fact, the inhibition of the transport enzyme Na-K-ATPase (30) suggests the occurrence of a defective ATP synthesis. In our study, major membranous changes were seen at the base of the cell where the Na-K-ATPase involved in active transport is localized (31)(32)(33)(34). While the brush border structure of the proximal nephron appeared to be well preserved (28,29) (35), who showed that maleic anhydride reacts rapidly and specifically with amino groups associated with the protein fraction of the red cell membrane.…”
Section: Introductionmentioning
confidence: 80%
“…Cytochemical studies have indicated enzymic polarity on the cell surface of intestinal epithelial cells (Nachlas et al, 1960), kidney, pancreas and mammary-gland cells (de-The, 1968). Plasmamembrane subfractions that represent the resolution of this polarity to varying degrees have been prepared from intestinal epithelium (Fujita et al, 1973), kidney proximal tubule (Heidrich et al, 1972), the electroplax organ (Duguid & Raftery, 1973), blood platelets (Barber & Jamieson, 1970) and cultured hepatocytes (Perdue et al, 1971).…”
Section: Bile-canicularfacementioning
confidence: 99%
“…The kidney tissue from male Sprague-Dawley rats (300 g) was homogenized and fractionated according to the scheme in [4] up to the pre-free flow electrophoresis stage (fraction Ps). Homogenization buffer consisted of 10 mM triethanolamine-HCl (pH 7.5) containing 0.25 M sucrose (TS buffer).…”
Section: Resultsmentioning
confidence: 99%